Proximal to distal cell communication in the Drosophila leg provides a basis for an intercalary mechanism of limb patterning. - Goto, S.; Hayashi, S. (Development, 1999)
Proximodistal patterning in the Drosophila leg is elaborated from the circular arrangement of the proximal domain expressing escargot and homothorax, and the distal domain expressing Distal-less that are allocated during embryogenesis. The distal domain differentiates multiply segmented distal appendages by activating additional genes such as dachshund. Secreted signaling molecules Wingless and Decapentaplegic, expressed along the anterior-posterior compartment boundary, are required for activation of Distal-less and dachshund and repression of homothorax in the distal domain. However, whether Wingless and Decapentaplegic are sufficient for the circular pattern of gene expression is not known. Here we show that a proximal gene escargot and its activator homothorax regulate proximodistal patterning in the distal domain. Clones of cells expressing escargot or homothorax placed in the distal domain induce intercalary expression of dachshund in surrounding cells and reorient planar cell polarity of those cells. Escargot and homothorax-expressing cells also sort out from other cells in the distal domain. We suggest that inductive cell communication between the proximodistal domains, which is maintained in part by a cell-sorting mechanism, is the cellular basis for an intercalary mechanism of the proximodistal axis patterning of the limb.